2020
DOI: 10.35371/aoem.2020.32.e25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of job stress on symptoms of bipolar spectrum disorder in an electronic parts manufacturing company

Abstract: Background Mental illness is known to be caused by genetic, biological, and environmental risk factors. Although previous studies have established the link between mental illness and job stress, most of them are limited to major depression disorder. Therefore, this study examined the relationship between job stress and bipolar spectrum disorder (BSD). Methods This is a cross-sectional study based on a survey conducted in April 2017 at an electronic parts manufacturing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A other study about BD and job strain (Oh, Kim, Ha & Kim, 2020, p. 8) found that “job stress increases the risk of BD”.…”
Section: Discussionmentioning
confidence: 97%
“…A other study about BD and job strain (Oh, Kim, Ha & Kim, 2020, p. 8) found that “job stress increases the risk of BD”.…”
Section: Discussionmentioning
confidence: 97%
“…Individuals with bipolar disorder are also more likely to report job stress, employment insecurity and dislocation, and need for disability payment when compared to the general population 316 . Moreover, job-related stress is often identified as an antecedent of relapse and chronicity of illness.…”
Section: Recent Environmental Exposures and Relapse Triggersmentioning
confidence: 99%